Critical Analysis of Da'if Hadiths in the Books of Ṣaḥīḥ Al-Albānī: Methodological Implications for Digital Hadith Platforms and Religious Authority in Indonesia - Hadi, Sofyan; Kosasih, Engkos; Darmawan, Dadang (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
Digital hadith platforms in Indonesia, adopting Muḥammad Nāṣir al-Dīn al-Albānī’s unverified ṣaḥīḥ/ḥasan assessments from his ten compilations, have eroded traditional scholarly authority and sparked controversies. This study analyzes 50 sample hadiths to: (1) identify ʿilal (hidden defects) and shudhūdh (anomalies) per mutaqaddimīn criteria; (2) classify Al-Albānī as mutasāḥil, mutashaddid, or muʿtadil; (3) compare his methods with mutaqaddimīn/mutaʼakhkhirīn; and (4) assess digital impacts on ʿilal methodology, authority shifts (jamāʿī to fardī), and religious practice. The framework integrates Grand Theory (mutaqaddimīn ʿilal/shudhūdh), Middle Range Theory (methodological dialectics), and Applied Theory (digital hadith authority). Using qualitative-library research via Manhaj al-Taḥqīq al-Muqāran, Five-Dimensional Criticism (5 Mīm), and Digital Verification Framework (5 Tāʼ), findings reveal seven sanad ʿilal types (e.g., ḏaʿfu al-rāwī 96%, tafarrud 80%) and three matn types (e.g., mukhālafah 28%), confirming mutaqaddimīn superiority via jamʿu al-ṭuruq. Twelve systemic errors (al-Anmāṭ al-Iṯhnā ʿAshara) classify al-Albānī as mutasāḥil fī al-taṣḥīḥ wa al-taḥsīn, amplified digitally to shift authority and practice. Recommendations urge diverse assessments on platforms, enhanced ʿilal curricula, and critical literacy. Contributions include Manhaj al-Taḥqīq al-Muqāran and al-manẓūmah al-Sufūyāniyyah for the preservation of the digital Sunnah.